Efficient Perovskite Solar Cells Based on a Solution Processable Nickel(II) Phthalocyanine and Vanadium Oxide Integrated Hole Transport Layer. Issue 14 (20th April 2017) - Cheng, Ming; Li, Yuanyuan; Safdari, Majid; Chen, Cheng; Liu, Peng; Kloo, Lars; Sun, Licheng
Abstract : An organic–inorganic integrated hole transport layer (HTL) composed of the solution‐processable nickel phthalocyanine (NiPc) abbreviated NiPc‐(OBu)8 and vanadium(V) oxide (V2 O5 ) is successfully incorporated into structured mesoporous perovskite solar cells (PSCs). The optimized PSCs show the highest stabilized power conversion efficiency of up to 16.8% and good stability under dark ambient conditions. These results highlight the potential application of organic–inorganic integrated HTLs in PSCs. Abstract : A perovskite solar cell containing a NiPc‐(OBu)8 and V2 O5 based organic–inorganic integrated hole transport layer is reported. It achieves a power conversion efficiency of 17.6%.